Pengembangan Panduan Praktikum Ipa Berbantuan Laboratorium Virtual Phet Pada Sub Materi Asam Basa Untuk Siswa Kelas VII SMP/MTs - megawati, megawati; Anwar; Novia Anugra (Program Studi Tadris IPA IAIN Parepare, 2025)
The problem underlying this research is the lack of understanding and interest of students in the science learning process and the lack of learning media used as open materials at SMPN 7 Polewali. Therefore, one effort that can be done is to develop LKPD based on a scientific approach so that students can follow or understand, and be interested in the science learning process. This study aims to determine the design of LKPD development, the feasibility of LKPD and student responses to LKPD based on the developed scientific approach. The type of research used is research and development (Research and development) which refers to the ADDIE model. The object used in this study is the Student Worksheet (LKPD) with the stages of analysis, design, development, implementation and evaluation of the instruments used in this study are validation sheets and student response questionnaires. The results of the study show that: (1) the design of the development of LKPD based on a scientific approach is in the very feasible category, (2) the feasibility of LKPD based on a scientific approach as assessed by media design experts is in the very feasible category (86%), material experts are in the very feasible category (86%) and student responses are in the very feasible category (90%). Thus, it can be concluded that Student Worksheets (LKPD) based on a scientific approach can be used as learning materials in the learning process.